The white hare - Fishwick, Michael (Zephyr, 2017)
Everything changed when Robbie's mother died--suddenly, he is uprooted and moved to Somerset, where he must pretend to play happy families with his dad and his new girlfriend. However, his new village comes with the mystery of the white rabbit, magical and swift in the silver moonlight, who leads Robbie and his new friends into a legend, chase, or hunt--the answer to the question of who is the hunter and who the hunted will solve all.